Energy in the Context of Sustainability - Bierbaum, Rosina M. and Matson, Pamela A. (Daedalus, 2013)
Today and in the coming decades, the world faces the challenge of meeting the needs of a still-growing human population, and of doing it sustainably – that is, without affecting the ability of future generations to meet their needs. Energy plays a pivotal role in this challenge, both because of its importance to economic development and because of the myriad interactions and influences it has on other critical sustainability issues. In this essay, we explore some of the direct interactions between energy and other things people need, such as food, water, fuel, and clean air, and also some of its indirect interactions with climate, ecosystems, and the habitability of the planet. We discuss some of the challenges and potential unintended consequences that are associated with a transition to clean, affordable energy as well as opportunities that make sense for energy and other sustainability goals. Pursuing such opportunities is critical not just to meeting the energy needs of nine billion people, but also to meeting their other critical needs and to maintaining a planet that supports human life in the near and long term.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDAxOTE